ANALISIS AKAD MURABAHAH TERHADAP PEMBIAYAAN KPR BTN BERSUBSIDI IBDI BANK BTN SYARIAH - Faradhiba, Yulia; Bahri, Andi; Damirah, Damirah; Muliati, Hj.; Semaun, Hj. Syahriyah (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
In BTN Sejahtera iB KPR financing, one of the obligations given by the bank to subsidized Sharia KPR customers is to pay home ownership credit before the 20th of each month. In providing subsidized Sharia KPR financing, BTN Syariah Parepare collaborates with subsidized housing in Parepare City. The aim of this research is to analyze murabahah contracts for sharia mortgage financing for subsidized housing, a case study at Bank BTN Syariah Parepare. This study used qualitative research methods. The location of this research is Bank BTN Syariah Parepare City Branch. The interviewees were 3 people from marketing at Bank BTN Syariah, Parepare City and 10 customers of Bank BTN Syariah, Parepare City, who took subsidized mortgages. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The research results show that the forms of financing at the BTN Syariah Bank in the city of Parepare are divided into three, namely FLPP (Housing Financing Liquidity Facility), Public Housing Savings (TAPERA), and Savings-based housing financing assistance (BP2BT). Where Islamic banks provide financing with the aim of obtaining income and helping customers or other communities who need these financing funds in developing their various businesses so that the economy becomes prosperous